Investigations on laser splicing of optical fibers - Lee, Yee Boey. (2008)
This thesis presents studies conducted on a unique and relatively unexplored technique for splicing of optical fibers using lasers. In the field of optical communications, the importance of fiber splicing as an important practical tool needs no emphasis. Although lasers are extensively employed in a variety of material processing applications (such as soldering, bonding etc.) their potential for optical fiber splicing has not been investigated. This thesis contains some of our findings on the laser splicing technique and discusses the key features of possible approaches to the proposed technique.